1995
DOI: 10.1083/jcb.131.6.1759
|View full text |Cite
|
Sign up to set email alerts
|

Dominant negative effect of cytoplasmic actin isoproteins on cardiomyocyte cytoarchitecture and function.

Abstract: Abstract. The intracompartmental sorting and functional consequences of ectopic expression of the six vertebrate actin isoforms was investigated in different types of cultured cells. In transfected fibroblasts all isoactin species associated with the endogenous microfilament cytoskeleton, even though cytoplasmic actins also showed partial localization to peripheral submembranous sites. Functional and structural studies were performed in neonatal and adult rat cardiomyocytes. All the muscle isoactin constructs … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
71
1

Year Published

1996
1996
2001
2001

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 92 publications
(80 citation statements)
references
References 57 publications
6
71
1
Order By: Relevance
“…Transfected ␣-SMA was predominantly incorporated into stress fibers as evaluated by double-labeling with antibodies against ␣-SMA and against the VSV-G-tag at the actin C terminus ( Figure 7B). Stably transfected ␣-cardiac ( Figure 7D) and transiently transfected ␤-cytoplasmic actin were also incorporated into stress fibers, but the latter occasionally accumulated in cytoplasmic aggregates if strongly overexpressed, a phenomenon reported previously for transfected primary cells (von Arx et al, 1995;Mounier et al, 1997). Transfected ␥-cytoplasmic actin predominantly localized in lamellipodia and membrane ruffles ( Figure 7C) and sporadically appeared in stress fibers of high expressing clones.…”
Section: Transfection With ␣-Sma Cdna Enhances Contraction Of 3t3 Fibsupporting
confidence: 80%
See 1 more Smart Citation
“…Transfected ␣-SMA was predominantly incorporated into stress fibers as evaluated by double-labeling with antibodies against ␣-SMA and against the VSV-G-tag at the actin C terminus ( Figure 7B). Stably transfected ␣-cardiac ( Figure 7D) and transiently transfected ␤-cytoplasmic actin were also incorporated into stress fibers, but the latter occasionally accumulated in cytoplasmic aggregates if strongly overexpressed, a phenomenon reported previously for transfected primary cells (von Arx et al, 1995;Mounier et al, 1997). Transfected ␥-cytoplasmic actin predominantly localized in lamellipodia and membrane ruffles ( Figure 7C) and sporadically appeared in stress fibers of high expressing clones.…”
Section: Transfection With ␣-Sma Cdna Enhances Contraction Of 3t3 Fibsupporting
confidence: 80%
“…The actin constructs used in our experiments were described by von Arx et al (1995) and their sorting in several cell types was reported previously (Mounier et al, 1997). For transient and stable transfections, we used a pCMV␤ vector (Clontech Laboratories AG, Basel, CH), in which the neomycin gene was cloned in EcoRI and in which the ␤-galactosidase gene was replaced by full-length cDNA encoding rat ␣-SMA, human ␥-and ␤-cytoplasmic actins, and chicken ␣-cardiac muscle actin.…”
Section: Actin Constructs and Transfectionmentioning
confidence: 99%
“…␤-actin does not substitute for muscle actin in either the formation of stress fibers (17) or myofibrils in cardiomyocytes (18). In addition, it seems to interact more tightly with certain actin binding proteins that may function at the leading edge of crawling cells.…”
Section: Discussionmentioning
confidence: 95%
“…All four muscle actins can incorporate into the thin filaments of cultured adult rat cardiomyocytes (41), and vascular smooth muscle ␣-actin is normally present in the sarcomeres of the developing heart (15,17). Similarly, both vascular smooth muscle and skeletal muscle ␣-actins can be detected in myofibrils (Fig.…”
Section: Discussionmentioning
confidence: 96%